2013
DOI: 10.1007/s00467-013-2635-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulatory network of renal primordium development

Abstract: Animal development progresses through the stepwise deployment of gene regulatory networks (GRN) encoded in the genome. Comparative analyses in different species and organ systems have revealed that GRN blueprints are composed of subcircuits with stereotypical architectures that are often reused as modular units. In this review, we report the evidence for the GRN underlying renal primordium development. In vertebrates, renal development is initiated by the induction of a field of intermediate mesoderm cells com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Because renal programming events may manifest as a low nephron endowment in diet-induced programming models [17], and because we previously observed that DEX can impair nephrogenesis [9], we analyzed a panel of genes that has previously been reported to be relevant to kidney development [18,19]. As shown in Table 2, Fgf10, Wt1, Gfra1, Eya1, Gata3, Kirrel, Etv4, Lhx1, Bmp2, and Cdh6 were found to be modified above the chosen threshold in the kidneys of 1-week-old offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Because renal programming events may manifest as a low nephron endowment in diet-induced programming models [17], and because we previously observed that DEX can impair nephrogenesis [9], we analyzed a panel of genes that has previously been reported to be relevant to kidney development [18,19]. As shown in Table 2, Fgf10, Wt1, Gfra1, Eya1, Gata3, Kirrel, Etv4, Lhx1, Bmp2, and Cdh6 were found to be modified above the chosen threshold in the kidneys of 1-week-old offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Since renal programming may manifest as a low nephron endowment in diet-induced programming models [2][3][4][5], literature was used to identify relevant target genes crucial for kidney development [16,17]. As shown in Table 3, Slit2, Spry3, Pod1, Col4a1, Col4a2, Col4a4, Wnt9b, Lif, Fgf2, Fgf20, Notch2, Jnk3 and Cdh6 were found modified above the chosen threshold in the kidney of offspring at 1 day of age to maternal HF exposure.…”
Section: Nephrogenesis-related Gene Expressionmentioning
confidence: 99%
“…Furthermore, epigenetic regulation is a proposed mechanism contributing to developmental programming [17]. We analyzed five groups of epigenetic regulators in the kidneys of offspring at 1 day of age to maternal HF diet.…”
Section: Gene Expression In Epigenetic Regulatorsmentioning
confidence: 99%
“…The Pax2/8-Gata3 cascade is therefore necessary to establish the responsiveness of the nephric duct to kidney induction. Interestingly, Pax2/8 from the nephric duct also act indirectly on the maintenance of Gdnf in the metanephric mesenchyme through the Pax2/8-Lhx1-Npnt cascade [50,64]. Epithelial Npnt is the ligand for mesenchymal α8β1 integrin [65].…”
Section: Page 11 Of 36mentioning
confidence: 97%
“…Pax genes act on this system at several distinct levels during kidney development ( Figure 2). In the nephric duct, Ret is a direct regulatory target of Gata3 [50,51,64]. The Pax2/8-Gata3 cascade is therefore necessary to establish the responsiveness of the nephric duct to kidney induction.…”
Section: Page 11 Of 36mentioning
confidence: 99%